1993
DOI: 10.1203/00006450-199303000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Resiliency to Amplification of Carbon Tetrachloride Hepatotoxicity by Chlordecone during Postnatal Development in Rats

Abstract: ABSTRACT. The interactive hepatotoxicity of C C 4 and chlordecone, at an individually nontoxic dosage, was studied in neonatal and young developing rats. The well-documented amplification of CCI4 (100 pL/kg) hepatotoxicity and lethality by prior dietary exposure to chlordecone (10 ppm, for 1 5 d) was absent in neonatal and developing rats through 3 5 d of age. The chlordecone-potentiated hepatotoxicity and lethality of C C 4 was partially expressed in 45-d-old rats and fully expressed in 60-d-old rats. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 18 publications
1
36
1
Order By: Relevance
“…14,15 Whereas 20-day-old newborns are completely resilient to a lethal combination of chlordecone ϩ CCl 4, 60-day-old adult rats exhibit 100% mortality. 15,16 Livers of 20-day-old rat pups examined in the current study showed remarkably high CAST expression as compared with the livers of 60-day-old adults (same controls used for the other two models of cell division investigated in the current study). These findings endorse the hypothesis that higher CAST in the dividing cells is essential to prevent progression of injury and acute liver failure on exposure to overdose of hepatotoxic drugs.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…14,15 Whereas 20-day-old newborns are completely resilient to a lethal combination of chlordecone ϩ CCl 4, 60-day-old adult rats exhibit 100% mortality. 15,16 Livers of 20-day-old rat pups examined in the current study showed remarkably high CAST expression as compared with the livers of 60-day-old adults (same controls used for the other two models of cell division investigated in the current study). These findings endorse the hypothesis that higher CAST in the dividing cells is essential to prevent progression of injury and acute liver failure on exposure to overdose of hepatotoxic drugs.…”
Section: Discussionmentioning
confidence: 93%
“…The 20-dayold male rat pups (NB) known to exhibit extensive liver growth during this early development [14][15][16] were chosen for this study.…”
Section: Models Of Liver Tissue Repair or Liver Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that neonate and postnatally developing rats are resilient to a wide variety of structurally and mechanistically dissimilar hepatotoxicants such as galactosamine, acetaminophen, allyl alcohol, and CC4 (49,(73)(74)(75)(76)(77)(78). Most interestingly, young rats survive exposure to the lethal combination of chlordecone and CC14, which causes 100% lethality in adult male and female rats (49,76,77).…”
Section: Resiliency Ofpostnatally Developing Ratsmentioning
confidence: 99%
“…Most interestingly, young rats survive exposure to the lethal combination of chlordecone and CC14, which causes 100% lethality in adult male and female rats (49,76,77). In a study where postnatally developing (20-and 45-day), and adult (60- Examination of growth factors and protooncogene expression revealed a 3-and 3.5-fold increase in TGF-a and H-ras mRNA expression, respectively, coinciding with maximal hepatocyte DNA synthesis in 20-day rats fed a normal diet, as opposed to only 2-and 2.5-fold increases observed in 60-day rats fed a normal diet, respectively (77).…”
Section: Resiliency Ofpostnatally Developing Ratsmentioning
confidence: 99%